Perancangan dan Implementasi Sistem Informasi Pada Rental Mobil di Era Pandemi - Muzaki, Akhmad Dian; Sumari, Arwin Datumaya W; Redhysyahputra, Irsyadha Alfyrdhousi; Gunawan, Rakha Elang (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
Car Rental Information System is an information system to support car rental activities for customers in the city and outside the city. In this information system, it is still using the traditional system which causes frequent errors in the data processing and is less efficient. This application was built to help process order data, which includes car rental payment transaction data, car order transaction data, car data, and generate detailed reports. The approach method used is structured and descriptive in nature with the case study approach, while the software in the development of this system is Java, MySQL Database, Browser and XAMPP. From the results of the application test, it can be seen that the Car Rental Information System application can provide convenience to customers in the car ordering process without having to worry about contracting the COVID-19 virus because the transaction process is carried out online, and for admins it can provide convenience in managing the ordering process. cars, reports and expenses.